Avaliação do potencial do líquido de sisal e do suco de caju para a produção de celulose bacteriana - Lima, Helder Levi Silva (2014)
Bacterial cellulose (BC) is an interesting biomaterial for researchers because it presents structure in nanoscale dimensions, high crystallinity degree, high porosity, biocompatibility, and high technological potential. Alternative carbon sources have been studied to replace traditional synthetic medium as a substrate for BC production, achieving satisfactory results. The aim of this work was to evaluate BC production using agro-industrial sources (sisal juice and cashew apple juice) as substrates in Gluconacetobacter hansenii ATCC 23769 cultivation under static conditions. The effects of sugars concentration, pH, and nitrogen sources supplementation were evaluated on the BC yield production. The efficiency of the BC purification process and the crystallinity degree of BC were also evaluated. The higher yield of BC was obtained after 10 days of cultivation in the medium based on sisal juice with the following parameters: 15 g/L of sugars, pH 5, and nitrogen supplementation with 7.5 g/L of yeast extract. When use cashew apple juice, the higher yield of BC was obtained after 5 days of cultivation in the medium with 50 g/L of sugars. The BC from the sisal juice medium presented similar TG, DSC, XRD, and FTIR characteristics to the BC from the standard medium. Thus, the sisal juice is a suitable substrate for BC production.